A review on bismuth-based materials for the removal of organic and inorganic pollutants. (November 2022) - Perumal, Suguna; Lee, Wonmok; Atchudan, Raji
Abstract: Modernized lifestyle and increased industrialization threaten living organisms because of the pollutants released from industries and household wastes. The presence of even small amounts of pollutants (organic pollutants (OPs) and inorganic pollutants-heavy metals (HMs)) shows significant effects. Thus wastewater treatment is urgently needed before being subjected to use. Many methods and materials have been developed and reported for the removal of pollutants from wastewater. This review focused on the removal of both OPs and HMs using bismuth-based (Bi-based) materials because of their low toxicity and excellent properties compared to other metals. Bi-based materials as a photocatalyst for photodegradation of OPs are discussed in detail with synthesis methods. Further, since few reviews are available on the Bi-based material for the removal and sensing of HMs, this topic was intentionally summarized. About 200 published articles and reviews have been reviewed here. Additionally, the key point that needs to be focused on the development of Bi-based photocatalysts for the removal of OPs and for upgrading the Bi-based materials as adsorbents for HMs are conferred in the outlook. This will help many researchers in their upcoming work. Graphical abstract: Image 1 Highlights: Organic (OPs) and inorganic (HMs) pollutants in water bodies are summarized. Removal of OPs and HMs from wastewater using Bi-based materials is discussed. The sensing efficacy of Bi-based materials toward HMs is discussed. Future work directed towards the development of Bi-based is proposed in outlook.